STRENGTHENING RESILIENCE: THE ROLE OF INSTITUTIONS IN FACILITATING LOCAL AGRICULTURAL ADAPTATION TO THE IMPACT OF CLIMATE CHANGE IN TANZANIA - Reginald Chetto; Makarius Mdemu; Jacob Kihila (Central European Journal of Geography and Sustainable Development)
Building resilience in areas susceptible to climatic hazards is widely recognised as a critical strategy. This article offers valuable insights into the contribution of institutions to supporting smallholder farmers in building resilience against the effects of climate change. Data for this article was collected from Manzase and Haneti villages in Chamwino district in Dodoma region, Tanzania. The study adopted a qualitative approach and deployed key informant interviews and focus group discussions for data collection. The result showed that institutions that operate in the villages under study which include agricultural extension agencies, Non-Governmental organisations, private companies and village governments, have played such roles as providing drought-resistant seeds, disseminating seasonal weather forecast information and supporting the establishment of income diversification activities to farmers. Furthermore, the institution facilitated agroforestry farming through natural tree regeneration and ensured access to crop markets and loans for farm inputs. These roles have contributed to reducing crop loss due to drought and rainfall unreliability, enhanced household income, and allowed households access to food during drought-induced crop failure. The study also revealed that institutional linkages are crucial in comprehensively addressing challenges faced by smallholder farmers, thereby building their livelihood resilience. This paper argues that strong institutional support is essential for farmers to build resilience against climate change.